Nursing Care of Patient's Family with Advance Nasopharynx Cancer: Case Report - Nurilhami, Ilham Taufik; Haroen, Hartiah; Agustina, Hana Rizmadewi (Jurnal Keperawatan Profesional (KEPO), 2025)
Nasopharyngeal Cancer (NPC) is a life-threatening illness. Early palliative care approach is essential to improve the quality of life of patients and families. However, in the clinical settings, health professionals often consider families as providers who provide care for patients. Whereas in palliative care the family is a unit of care that have to be seen as a patient who needs support. This article is a case report nursing care to a family of a patient with advanced nasopharyngeal cancer. It is found that family needs include physical, psychological and health information. Based on the literature, there are several assessment and intervention guidelines such as the CARES intervention framework that can be applied by nurses in providing palliative care approach to families, especially in the health care system.